CULTURAL CITIZENSHIP LITERACY LEARNING MODEL: THE ACQUAINTANCESHIP IN AN HOMOGENEOUS SOCIETY - Hamid, Solihin Ichas; Istianti, Tuti; Abdillah, Fauzi (International Journal of Psychosocial Rehabilitation, 2020)
This article describes a stage in exploring and developing a model of learning to iterate citizenship culture in elementary schools. Qualitative approaches and grounded theory in the R&D strategy are employed to follow up on the findings of the model developed by Cireundeu's School teachers through observation, interviews, and documentation, especially as a step of learning innovation in elementary schools with homogeneous sociographic environmental characteristics. The teacher's experience and the actions of learning development that he did base on the cultural citizenship literacy model became the scope of this study. The findings show that in a homogeneous sociographic context, teachers utilize many of the learning materials available in the community. Besides, students and schools get supplements from local traditions that are carried out in the school and home environment, so that teachers and students feel more familiar with traditional cultural and artistic expressions. From these findings, researchers obtained a set of models, media, and evaluation patterns of the learning process of innovation in the development of citizenship culture literacy. The tool will be used in elementary civic school lessons based on local traditions, which can be applied in multi-contexts with different local cultural richness and diversity. The recommendation of this research is the need for further research to try out learning tools that are adapted to the context of heterogeneous local traditions in the appropriate classroom environment.